Simulación del comportamiento micromecánico de aceros de fase dual por medio del método de elementos ﬁnitos (2020)
This work encompasses a DP600 steel mechanical behavior characterization by using micro indentation test simulations. To simulate the microindentation was used methodologies to generate bidimensional and tridimensional artificial representative volume elements (RVE) based on material's statistical data. There were selected micromechanical models to predict its phases' behavior. The experimental data to validate the behavior was found on literature then it was introduced on nano indentation and micro indentation simulations. Nano indentations were used to validate the individual phases' mechanical behavior later Micro indentations were made to study the effect of second phase particles immersed in the volume. The distribution of second phase particles shows an effect over the mechanical behavior on the simulation explaining the curves differences.